Maqashid Syariah Review of Inheritance Distribution Practices from Parents to Children in the Betawi Indigenous Community of Kapuk Village: A Socio-Legal Empirical Study - Diva Hardiyanti Abdillah; Muhammad Yusron (Sahaja: Journal Sharia and Humanities, 2025)
This study examines inheritance distribution practices among the Betawi indigenous community in Kapuk Village, West Jakarta, through the lens of maqashid syariah theory. Parents often distribute inheritance orally during their lifetime, based on personal discretion without formal documentation or witnesses, frequently excluding other family members. This practice raises concerns about fairness, familial conflicts, and potential violations of Islamic justice principles. Using an empirical legal research method with a socio-legal approach, data were collected through interviews with community leaders and family members, as well as secondary sources. The findings reveal that inheritance distribution often deviates from Islamic inheritance law (faraid), favoring children perceived as emotionally closer or more responsible. While this reflects local cultural values, it frequently leads to dissatisfaction and disputes among heirs, especially in the absence of formal documentation. However, this practice aligns with maqashid syariah by prioritizing maslahat (benefit), justice, and social stability. By emphasizing maslahat over strict adherence to textual rules, such practices are considered a legitimate form of ijtihad within Islamic law. This nuanced approach highlights the balance between cultural traditions and Islamic legal principles, suggesting that as long as fairness and social harmony are maintained, such practices can be justified under maqashid syariah.